Internet histories and computational methods: a "round-doc" discussion. Issue 3 (2nd October 2019) - Brügger, Niels; Milligan, Ian; Ben-David, Anat; Gebeil, Sophie; Nanni, Federico; Rogers, Richard; Turkel, William J.; Weber, Matthew S.; Webster, Peter
Abstract: This conversation brings together leading experts within the field of computational methods. Participants were invited to discuss "Internet histories and computational methods", and the debate focused on issues such as why scholars of internet histories should consider using computational methods, what scholars should be looking out for when they use these methods, how the process of collecting influences computational research, what impedes the use of computational methods, to what an extent internet historians should learn to code (or conversely, if developers should learn about historical methods), what are the most defining moments in the history of computational methods, and, finally, the future of using computational methods for historical studies of the internet.